Answer:
A) (-5, -34)
Explanation:
f(x) = x^2 + 10x - 9
We complete the square to get the equation in vertex form
Take the coefficient of the x term and divide by 2 then square it. We add it and then subtract it not to change the value of the equation
f(x) = x^2 + 10x +(10/2)^2 - (10/2)^2 - 9
f(x) = x^2 +10x +25 -25 -9
f(x) = (x^2 +10x +25) -34
The term in parentheses simplified to (x+10/2) ^2
= (x+5)^2 -34
= (x - -5)^2 -34
This is in the form (x-h)^2 +k
The vertex is (h,k) h=-5 and k=-34
(-5,-34)